Analysis Of Cash Ratio, Return on Assets, Debt to Equity Ratio and Earnings per Share Of Cash Dividend (Studies in Food and Beverage Subsector Company Listed in Indonesia Stock Exchange - Nungki Asri Saraswati; Juni Herawati (Jurnal Ilmiah Mahasiswa FEB, 2014)
This study aims to examine and analyze the effect of the cash ratio, return on assets,  debt  to  equity  ratio  and  earnings  per  share  of  the  cash  dividend  on  food  and beverage companies listed in Indonesia Stock Exchange. Secondary data were obtained from  the annual  financial statements  in  the  Indonesia Stock Exchange. The population in  this  study  amounted  to  21  food  and  beverage  companies  listed  in  Indonesia Stock Exchange in 2010-2013. The sampling method used is saturated sampling method. The samples studied a total of 11 companies. Based on the hypothesis testing is done using multiple  regression,  the  results  showed  that  independent variable  return  on  assets  and earnings  per  share  cash  dividend  significantly  influence  the  food  and  beverage companies listed in Indonesia Stock Exchange. Keywords:  Cash  Ratio,  Return  on  Assets, Debt  to  Equity  Ratio,  Earning  per  Share, Cash Dividend